Nephroprotective Effects of Synthetic Flavonoid Hidrosmin in Experimental Diabetic Nephropathy - Luna Jiménez-Castilla; Gema Marín-Royo; Macarena Orejudo; Lucas Opazo-Ríos; Teresa Caro-Ordieres; Inés Artaiz; Tatiana Suárez-Cortés; Arturo Zazpe; Gonzalo Hernández; Carmen Gómez-Guerrero; Jesús Egido (MDPI AG, 2021)
Diabetes mellitus (DM) is a high-impact disease commonly characterized by hyperglycemia, inflammation, and oxidative stress. Diabetic nephropathy (DN) is a common diabetic microvascular complication and the leading cause of chronic kidney disease worldwide. This study investigates the protective effects of the synthetic flavonoid hidrosmin (5-O-(beta-hydroxyethyl) diosmin) in experimental DN induced by streptozotocin injection in apolipoprotein E deficient mice. Oral administration of hidrosmin (300 mg/kg/day, n = 11) to diabetic mice for 7 weeks markedly reduced albuminuria (albumin-to-creatinine ratio: 47 ± 11% vs. control) and ameliorated renal pathological damage and expression of kidney injury markers. Kidneys of hidrosmin-treated mice exhibited lower content of macrophages and T cells, reduced expression of cytokines and chemokines, and attenuated inflammatory signaling pathways. Hidrosmin treatment improved the redox balance by reducing prooxidant enzymes and enhancing antioxidant genes, and also decreased senescence markers in diabetic kidneys. In vitro, hidrosmin dose-dependently reduced the expression of inflammatory and oxidative genes in tubuloepithelial cells exposed to either high-glucose or cytokines, with no evidence of cytotoxicity at effective concentrations. In conclusion, the synthetic flavonoid hidrosmin exerts a beneficial effect against DN by reducing inflammation, oxidative stress, and senescence pathways. Hidrosmin could have a potential role as a coadjutant therapy for the chronic complications of DM.